Association of Individual Risk Factors and Workplace Factors to Self-Reported Body Discomfort of Filipino Small-Scale Gold Miners - Custodio, Benette; Matias, Aura; Soriano, Virginia (Philippine Engineering Journal; Vol 39 No 1 (2018), 2018)
Abstract – Work-related Musculoskeletal Disorder (WMSD) was identified as a significant and costly health and safety problem for the large-scale mining industry. WMSD is often characterized by discomfort such as pain, tingling, numbness, stiffness, and aching perceived on the different body parts. The risk factors of WMSD in large scale mining can also be observed in small-scale gold mining. However, there is little information on the association of individual and workplace risk factors to the perceived body discomfort of the workers in the small-scale gold mining and extraction in the Philippines. This study aimed to provide a baseline data on the prevalence of body discomfort and its association to individual and workplace risk factors. To achieve this, a survey of 124 small-scale gold mining and extraction workers in seven different mining and extraction sites from selected regions in the Philippines was conducted. The results showed that ninety-five percent (95%) of the survey participants perceived body discomfort in at least one part of their bodies. The highest percentage of discomfort on body parts were on the lower back (65.32%), shoulders (59.68%), and neck (54.03%). Using correlation analysis, results showed that the severity of lower back discomfort and the estimated alcohol consumption per week has low positive correlation. Likewise, the frequency and severity of knee discomfort have a low positive correlation to years of experience in mining. Furthermore, by using binary logistic regression, it was found that drinking alcohol and the Rapid Entire Body Assessment (REBA) score which characterizes physical demand were found to be significantly associated with presence of discomfort on the lower back; years of experience in mining and estimated height were significantly associated to the presence of discomfort on the knees. Further analysis of workplace factors and other possible risk factors of the body discomfort is recommended.     Keywords—Body discomfort, Individual risk factors, Workplace risk factors, Filipino Small-Scale Gold Miners